Identification of Changes in Retinal Images of Animal Models of Alzheimer's Disease Using a Deep Learning Approach - Trindade, Rita Caetano (2021)
Dissertação de Mestrado Integrado em Engenharia Biomédica apresentada à Faculdade de Ciências e Tecnologia